La responsabilité de produits : un grand risque assurable - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1989)
With the growing sophistication of manufactured products, this brief article is an attempt ta examine product liability as a high risk, making liability insurance imperative for manufacturers, products designers, asbestos contractors, etc. In the U.S., the number of new bodily injury cases related to asbestos liability continues ta increase, presently exceeding 3,000 per month.